2018
DOI: 10.1002/eji.201747264
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of elastase stimulate murine B lymphocyte differentiation into IgG‐ and IgA‐producing cells

Abstract: It is well established that dendritic cells and macrophages play a role in antigen presentation to B and T cells and in shaping B and T cell responses via cytokines they produce. We have previously reported that depletion of neutrophils improves the production of mucosal IgA after sublingual immunization with Bacillus anthracis edema toxin as adjuvant. These past studies also demonstrated that an inverse correlation exists between the number of neutrophils and production of IgA by B cells. Using specific inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…We also tested whether NEI could regulate immune factors in other animal species. We previously showed that NEI stimulates the expression of BAFF and IL-10 and secretion of IgG and IgA by murine spleen cells, in vitro ( 25 ). Addition of NEI to cultures of pig spleen cells stimulated IgG and IgA secretion ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also tested whether NEI could regulate immune factors in other animal species. We previously showed that NEI stimulates the expression of BAFF and IL-10 and secretion of IgG and IgA by murine spleen cells, in vitro ( 25 ). Addition of NEI to cultures of pig spleen cells stimulated IgG and IgA secretion ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NEI induction of antibody-stimulating cytokines BAFF and IL-10 ( SI Appendix , Fig. S3 ) ( 25 ) could be the accelerating factor. NEI supplementation or lack of elastase could facilitate the migration of vaccine-primed cells, as suggested by others who showed that depletion of neutrophils favors the development of T responses at distant lymph nodes ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the inactivated B cells are stimulated by an antigen via IgM, these cells undergo Ig class switching recombination (CSR) to produce antibodies of different isotypes but having the same antigen specificity as IgM, such as IgA and IgG ( 29 ). Many cells provide the costimulation and cytokine signals required by IgCSR and B cells to produce antibodies ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the targeting peptide of M cells and the DCs favored the T h 1-cell response (54), which stimulates the expansion of germinal center B cells for anti-ETEC-specific antibody production (55). It is well established that DCs and macrophages play a role in antigen presentation to Band T-cells and in shaping B and T cell responses to produce mucosal IgA after sublingual immunization with Bacillus anthracis edema toxin as an adjuvant (56). Various studies have shown that antigens target different molecules, which results in different immune responses.…”
Section: Discussionmentioning
confidence: 99%